Pengaruh Manajemen Modal Kerja Terhadap Profitabilitas: (Studi Empiris pada Perusahaan IDX30 yang Terdaftar di Bursa Efek Indonesia Periode 2020-2024) - Siti Luthfiani; Sugeng Priyanto (MANAJEMEN, 2026)
This study aims to analyze the effect of working capital management on profitability in companies listed in the IDX30 index during the period 2020–2024. Working capital management is proxied by Working Capital Turnover (WCTO), Cash Turnover (CTO), Accounts Receivable Turnover (ARTO), and Inventory Turnover (ITO), while profitability is proxied by Return on Assets (ROA). The sample consists of 10 companies selected using purposive sampling based on predetermined criteria, resulting in 50 observations obtained from the official website investing.com. The data were analyzed using multiple linear regression with SPSS version 22. The results indicate that Working Capital Turnover (WCTO) and Inventory Turnover (ITO) have a significant negative effect on Return on Assets (ROA), while Cash Turnover (CTO) has a significant positive effect on Return on Assets (ROA). In contrast, Accounts Receivable Turnover (ARTO) does not have a significant effect on Return on Assets (ROA). These findings suggest that efficient working capital management, particularly in terms of cash turnover, contributes positively to company profitability, while inefficiencies in working capital and inventory turnover may reduce profitability.